2018
DOI: 10.1016/j.neuropharm.2017.09.036
|View full text |Cite
|
Sign up to set email alerts
|

A hypothalamo-midbrain-medullary pathway involved in the inhibition of the respiratory chemoreflex response induced by potassium cyanide in rodents

Abstract: To cite this version:Tabinda Zafar, Charly Brouillard, Laurence Lanfumey, Caroline Sévoz-Couche. A hypothalamomidbrain-medullary pathway involved in the inhibition of the respiratory chemoreflex response induced by potassium cyanide in rodents.Neuropharmacology, Elsevier, 2017Elsevier, , 10.1016Elsevier, /j.neuropharm.2017 Accepted Manuscript A hypothalamo-midbrain-medullary pathway involved in the inhibition of the respiratory chemoreflex response induced by potassium cyanide in rodents This is a PDF file … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Previously we showed that the baroreflex inhibition induced by the dorsolateral PAG involved the activation of NTS 5‐HT 3 receptors (Bernard et al, 2008; Comet et al, 2004, 2005; Sévoz‐Couche et al, 2003). Both the microinjection of granisetron into the NTS and the use of mice lacking the 5‐HT 3 receptor prevented dorsolateral PAG‐induced inhibition of chemoreflex responses (Zafar et al, 2018). In the same manner, the cuneiform‐induced baroreflex inhibition was prevented by the blockade of NTS 5‐HT 3 receptors with granisetron and was also not observed in 5‐HT 3 receptor knockout mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously we showed that the baroreflex inhibition induced by the dorsolateral PAG involved the activation of NTS 5‐HT 3 receptors (Bernard et al, 2008; Comet et al, 2004, 2005; Sévoz‐Couche et al, 2003). Both the microinjection of granisetron into the NTS and the use of mice lacking the 5‐HT 3 receptor prevented dorsolateral PAG‐induced inhibition of chemoreflex responses (Zafar et al, 2018). In the same manner, the cuneiform‐induced baroreflex inhibition was prevented by the blockade of NTS 5‐HT 3 receptors with granisetron and was also not observed in 5‐HT 3 receptor knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…Anaesthetized animals were placed in a stereotaxic frame with the head fixed in the flat skull position. The size of the samples was based on previous experiments (Bernard et al, 2008; Netzer et al, 2011; Zafar et al, 2018). Briefly, rostral cuneiform disinhibition was caused by left microinjection of bicuculline in rats (50 pmol per 50 nl, n = 30, n = 6 in each of 5 groups: [i] B3 muscimol, [ii] B3 8‐OH‐DPAT, [iii] B3 saline, [iv] NTS granisetron, and [v] NTS saline) and mice (25 pmol per 25 nl, n = 6 WT and n = 6 5‐HT 3 knockout animals).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nucleus tractus solitarii (NTS) receives visceral sensory information and integrates these information to orchestrate autonomic functions such as blood pressure, 1 breathing 2 and gut motility. 3 The NTS not only integrates information from peripheral receptors, but also receives inputs from central nervous systems, such as brainstem, 4 hypothalamus, 5 and limbic system. 6 Meanwhile, NTS neurons extend their axons to numerous brain regions, 7 , 8 , 9 endowing the NTS with the remarkable ability to modulate multiple physiological functions.…”
Section: Introductionmentioning
confidence: 99%